Thermal comfort formation of the bus interior depending on the power unit layout - Holenko, K.; Voichyshyn, Y.; Horbai, O.; Burian, M.; Popovych, V.; Makovkin, O. (Problems of Tribology, 2022)
Energy consumption and thermal comfort are among the issues that research engineers of heating, ventilation and air conditioning systems deal with when investigating the most feasible solutions for their implementation. Existing methods of thermal comfort assessment are not optimized in two important and interrelated aspects: achieving thermal comfort (a) at the lowest possible energy consumption (b). Thermal comfort is situationally achieved when occupants perceive the ambient temperature, humidity, air movement and thermal radiation as ideal and do not prefer warmer or colder air or a different humidity level. Thermal comfort is defined by ASHRAE Standard 55 as a subjective concept characterized by the sum of sensations that create physical and mental well-being in a person. That is, he/she is in a state in which he/she feels comfortable and does not need to change one or more environmental parameters. Many studies have been conducted according to the international standards for thermal comfort in vehicles. The presence of a large number of people in the bus leads to a deterioration of the air quality in its interior. The loss of quality is mainly caused by gases resulting from breathing and other organic particles. The presence of moisture, combustion products, particles can also reduce the air quality in the interior. Air quality is affected by the design features of heating, ventilation and air conditioning systems, which largely depend on the location of the power unit, which is the subject of the research. The influence of the bus engine layout is analysed in the presented work: for the rear-engine layout, the location of the engine vertically in the interior and other cases are also considered. Special fans are installed in the engine compartment to remove heat emitted by the engine.